0368 Pain Severity as a Moderator of the Association between Prescription Opioid Use and Insomnia Symptoms among Adults with Chronic Pain. (27th April 2018) - Miller, M B; Chan, W S; Boissoneault, J; Robinson, M; Staud, R; Berry, R B; McCrae, C S
Abstract: Introduction: Research documenting the impact of opioid medication on sleep among individuals with chronic pain has been mixed. This study aimed to determine if pain severity moderates the association between opioid dose and insomnia symptoms among adults with insomnia and chronic pain. Methods: Participants ( N =199; 95% women; 78% White; mean age=51.5, SD=11.6) completed daily diaries assessing insomnia symptoms and use of opioid pain medication for 14 days. Multiple regression was used to determine if evening pain severity moderates the association between average daily opioid dose and average daily sleep onset latency (SOL), wake after sleep onset (WASO), sleep quality (SQ), or time in bed (TIB). Analyses controlled for gender and use of sleep medication. Results: Opioid dose and pain severity interacted in the prediction of SOL ( B =-0.34, SE =0.16, p =.04) and TIB ( B =-0.81, SE =0.32, p =.01). Larger opioid dose was associated with longer SOL in the context of mild ( B =14.89, SE =4.83, p =.002) to moderate ( B =8.49, SE =3.07, p =.01) but not severe pain ( B =2.10, SE =3.88, p =.60). Similarly, larger opioid dose was associated with longer TIB in the context of mild ( B =31.70, SE =9.40, p <.001) to moderate ( B =16.34, SE =5.98, p =.01) but not severe pain ( B =0.99, SE =7.55, p =.90). Opioid dose and pain severity did not interact in the prediction of WASO or SQ. Individuals with more severe pain reported significantly worse WASO and SQ than those with mild/moderate pain. Conclusion: Consistent with previous studies, opioids were associated with more difficulty falling asleep among adults with chronic pain. However, this effect was only significant among those reporting mild/moderate (as opposed to severe) pain. We speculate that this effect is masked among those with severe pain because the sleep debt they acquire throughout the night then facilitates sleep onset the next day. Support (If Any): This research was supported by the National Institute of Arthritis and Musculoskeletal and Skin Diseases (R01AR055160 and R01AR005160-S1; McCrae, PI). Data were collected as part of clinical trial NCT02001077 Sleep and Pain Interventions (SPIN) at the University of Florida (McCrae, PI).